2019
DOI: 10.3390/ijerph16244909
|View full text |Cite
|
Sign up to set email alerts
|

Interactive Improvements of Visual and Auditory Function for Enhancing Performance in Youth Soccer Players

Abstract: We analyzed the effects of a regular training program on the health- and skill-related physical fitness (PF) of talented soccer players aged < 12 years; visual reaction time (VRT) and auditory reaction time (ART) were also assessed. In this single-group interventional study, 78 talented male youth soccer players (mean age, 9.54 years) were critically selected by the Korean Educational Development Institute and underwent a 22-week training program consisting of 16 weeks of PF and basic skill training (90 min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…11 These results suggest RT may provide important information about musculoskeletal injury risk, and it is possible a more functional, sport-like RT assessment may be more sensitive to injury risk than stationary clinical RT. Given the associations between RT and sport performance, 3,4 incorporating functional RT assessments may better identify performance deficits that could be improved through targeted rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 These results suggest RT may provide important information about musculoskeletal injury risk, and it is possible a more functional, sport-like RT assessment may be more sensitive to injury risk than stationary clinical RT. Given the associations between RT and sport performance, 3,4 incorporating functional RT assessments may better identify performance deficits that could be improved through targeted rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
“…2 Quicker RT is associated with better professional baseball batting performance 3 and improved sport performance in elite youth soccer players. 4 RT is often assessed clinically in a stationary manner, but during sport, athletes react in a highly dynamic environment with ever-changing physical and mental stimuli. Functional RT is not correlated with clinically assessed RT, 5 but the reliability of this functional RT battery is unclear, impacting its clinical utility.…”
mentioning
confidence: 99%
“…Additionally, studies from the pre-COVID-19 period on soccer players’ visual skills were categorized as “performance” ( Song et al, 2019 ; Bekris et al, 2020 ). However, during the COVID-19 pandemic, the Topic Area “Performance-Visual Skill” disappeared, and cognitive keywords that are important in visual-skill research emerged, which could be interpreted as a topic area in the field of psychology ( Casella et al, 2022 ; Knollner et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this variability seems to be influenced by the healthy lifestyle, in terms of a relationship with biological markers, such as forced expiratory volume at one second, grip strength, and vision [ 34 ]. In contrast, many studies have undoubtedly shown that RT values are negatively influenced by various pathological conditions [ 46 , 47 ] and positively by the active lifestyle and training for physical fitness [ 39 , 48 ]. Consistent with the above-mentioned information, the novelty of our study refers to the relatively simple method of determining the RT variability by the Poincaré plot method, bringing to light the concept of nonlinear dynamics, which can explain, at least partially, our results.…”
Section: Discussionmentioning
confidence: 99%